Analysis The Influence of Instagram @Humas_Bandung Social Media Content on Public Opinion - Nur Fitri, Aisyah Dzakiah; Imran, Ayub Ilfandy (Jurnal Ilmiah Komunikasi Makna, 2024)
Digital progress has positive and negative effects on society, with social media, especially Instagram, playing a key role in information dissemination. People form opinions based on the content they encounter online.One of them is the content on the @humas_bandung Instagram account which provides content for the public every day. This research was conducted to find out how much influence Instagram @humas_bandung social media content has on public opinion. There is one theory and one model used, namely the theory of The Circular Model of SoMe and the Model of the opinion formation process. The author uses quantitative research methods by distributing questionnaires via Instagram and Whatsapp addressed to 100 Instagram followers @humas_bandung. The data analysis techniques used in testing variables are descriptive analysis, normality test, simple linear regression analysis, coefficient of determination, and hypothesis testing. The results showed that there was an influence of Instagram @humas_bandung social media content on public opinion. Based on the coefficient of determination, the social media content variable (X) has an effect of 59.7% on public opinion (Y). Meanwhile, 40.3% is influenced by other factors that are not included in this study.